2015
DOI: 10.1007/s00210-015-1172-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of CYP2A5 in liver injury and fibrosis: chemical-specific difference

Abstract: Liver injuries induced by carbon tetrachloride (CCL4) or thioacetamide (TAA) are dependent on cytochrome P450 2E1 (CYP2E1). CYP2A5 can be induced by TAA but not by CCL4. In this study, liver injury including fibrosis induced by CCL4 or TAA were investigated in wild type (WT) mice and CYP2A5 knockout (cyp2a5−/−) mice as well as in CYP2E1 knockout (cyp2e1−/−) mice as a comparison. Acute and sub-chronic liver injuries including fibrosis were induced by CCL4 and TAA in WT mice but not in cyp2e1−/− mice, confirming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
0
19
2
1
Order By: Relevance
“…This result is in contrast to many studies which reported increased levels of CYP2E1 expression in human specimens and animal models of NAFLD1214151617. This led us to assume that the presence of CYP2E1 even at basal levels might be adequate enough to induce the hepatic damaging effect through a permissive role to either upregulate other proteins or mediate their damaging effects, as reported32. Recently, following the use of high cholesterol diet (HCD), iNOS was upregulated, and was suggested as an important mediator of liver fibrosis since it was developed in WT mice, but not in iNOS -null fed HCD mice11.…”
Section: Discussioncontrasting
confidence: 74%
“…This result is in contrast to many studies which reported increased levels of CYP2E1 expression in human specimens and animal models of NAFLD1214151617. This led us to assume that the presence of CYP2E1 even at basal levels might be adequate enough to induce the hepatic damaging effect through a permissive role to either upregulate other proteins or mediate their damaging effects, as reported32. Recently, following the use of high cholesterol diet (HCD), iNOS was upregulated, and was suggested as an important mediator of liver fibrosis since it was developed in WT mice, but not in iNOS -null fed HCD mice11.…”
Section: Discussioncontrasting
confidence: 74%
“…We used our singleCellNet tool to cluster the day 4 and day 6 EB cells separately (manuscript in preparation). singleCellNet performs dimension reduction on the most variable genes by Principle Component Analysis (PCA), then uses hierarchical clustering and cutree (Becker et al, 1988), partitioning among medoids (PAM) (Kaufman and Rousseeuw, 1990), density peak finding (Rodriguez and Laio, 2014), and optionally, mclust (Scrucca et al, 2016) to assign cells to distinct clusters. singleCellNet selects the clustering that maximizes a metric of cluster quality, the average silhouette (Rousseeuw, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…CCL4- and TAA-induced liver injuries are CYP2E1-dependent because acute liver injury induced by CCL4 or TAA was observed in WT mice but not in the cyp2e1 −/− mice [43, 44]. We treated mice with CCL4 or TAA twice a week for 1 month to induce liver fibrosis and found that CCL4 or TAA induced chronic liver injury and liver fibrosis in WT mice but not in cyp2e1 −/− mice [45]. These results indicate that CYP2E1 metabolism is indispensable for CCL4- and TAA-induced liver injury, either acute or chronic.…”
Section: Cyp2e1 and Pathogenesis Of Alcoholic Liver Diseasementioning
confidence: 99%
“…As discussed above, the Lieber-decarli ALD animal model does not induce evident liver fibrosis. We applied CCL4 and TAA models to test whether CCL4- and TAA-induced liver fibrosis may be enhanced in cyp2a5 −/− mice compared with WT mice [45]. Acute liver injury induced by one single injection of CCL4, either higher dose or lower dose, was comparable in cyp2a5 −/− mice and WT mice; chronic liver injury and liver fibrosis induced by multiple injection for one month were comparable, too.…”
Section: Cyp2a5 and Liver Fibrosismentioning
confidence: 99%